Analysis of reasons for graduation from students of the Faculty of Mathematics and Science KTU - Morkevičiūtė, Miglė; Kravčenkienė, Violeta (Lietuvos matematikos rinkinys, 2019)
This article provides an overview of data from the Ministry of Education, Science and Sport of the Republic of Lithuania on students of Lithuanian higher education institutions. Data from Kaunas University of Technology studies department in 2016–2018 on student graduation, maturity exam and study module results has been analyzed. Using descriptive statistics, correlation, logistic regression analysis, and analyzing student interviews and interviews with the employees from the Faculty of Mathematics and Natural Sciences, it has been clariﬁed how achievements in school inﬂuence the ﬁnal marks of study modules and the success of studies overall.